中朝古代桃花源文学比较研究 = A comparative study of peach blossom literature in ancient China and Korea - 蔡佳敏 Cai, Jiamin (2015)
Peach blossom (Tao-yuan) is commonly depicted as a utopia that is isolated from the politics. This peach blossom imagery develops from Tao Yuan Ming's portrayal of a peach blossom in his famous poetry "The Peach Colony" ("Tao Hua Yuan Shi with Ji"). However, a utopia isolated from the politics is not the only cultural connotation that the peach blossom imagery suggests. In addition, the literary works comprising of the peach blossom imagery is not exclusively created by ancient Chinese poets, but also frequently seen in ancient Korean's compositions. Based on the above concerns, this paper directs its focus on the literary pieces comprising of the peach blossom imagery, and analyzes how ancient Chinese and Korean poets illustrate the peach blossom with an elaboration on the landscape, the upheaval and the retiracy, all of which are based on Tao Yuan Ming's portrayal. On the other hand, other than being influenced by Tao Yuan Ming, a noticeable amount of literary works went beyond the mere acceptance of Tao Yuan Ming's portrayal, and this is evident in two situations. Firstly, some Chinese and Korean poets expressed their doubt as to whether the peach blossom indisputably exists in the reality. Secondly, Korean poets went further than acceptance or uncertainty towards the peach blossom free from politics, and proposed a peach blossom that is either accessible through somnambulating in the psychological state, or incorporates politics that is benevolent (known as "ren zheng" in Mencius' thought), and these are seemingly perspectives yet to be explored by the Chinese poets. Therefore, based on the analysis and companson of the peach blossom literature between ancient China and Korea, this paper established a reception chain comprising of three different levels, namely "acceptance", "uncertainty" and "innovation", from which illustrating the different level in which Chinese and Korean poets arrived at, and thus gathering the results of this comparative study.